Dose-finding studies of pazufloxacin mesilate on bacterial pneumonia - Shimada, Kaoru (Japanese Journal of Chemotherapy, 2000)
Dose-finding studies of a novel new quinolone for injection, pazufloxacin mesilate (PZFX mesilate) were undertaken for bacterial pneumonia. The three-arm comparative trials were conducted in a random manner with ceftazidime (CAZ) as a control agent. The dose regimen of PZFX mesilate (PZFX-600 or PZFX-1000arm) was 600 mg or 1, 000 mg twice a day for 14 days and that of CAZ (CAZ arm) was 2, 000 mg twice a day for 14 days. 1) Subjects for analysis: A total of 120 cases were studied, consisting of 40 patients given PZFX-600, 39 given PZFX-1000, and 41 given CAZ. Among them, 91 cases were selected for analysis of clinical effect (PZFX-600: 33, PZFX-1000: 28, CAZ: 30 cases), 110 cases for analysis of adverse effects (PZFX-600: 37, PZFX-1000: 35, CAZ: 38 cases), 101 cases for abnormal laboratory values (PZFX-600: 35, PZFX-1000: 31, CAZ: 35 cases), and 87 cases for usefulness (PZFX-600: 31, PZFX-1000: 26, CAZ: 30 cases). 2) Clinical effect: Clinical efficacy rates were 100%(33 33) for PZFX-600, 92.9% for PZFX-1000 (26 28), and 93.3%(28 30) for CAZ. 3) Bacteriological effect: Bacteriological eradication rates were 93.3%(14 15) for PZFX-600, 100%(7 7) for PZFX-1000, and 100%(11 11) for CAZ. Streptococcus pneumoniae persisted in one PZFX-600 case. 4) Safety: The occurrence of adverse effects was 0%(0 37) for PZFX-600, 2.9%(1 35) for PZFX-1000, and 2.61%(1 38) for CAZ. None of the events were serious. The rate of laboratory abnormal valuse was 14.3%(5 35) for PZFX-600, 22.6%(7 31) for PZFX-1000, and 31.4%(11 35) for CAZ. Transaminase elevation and eosinophilia were the major incidents, although they were all mild. 5) Usefulness: The usefulness rate was 100%(31 31) for PZFX-600, 92.3%(24 26) for PZFX-1000, and 93.3%(28 30) for CAZ. There were no statistically significant differences among the three groups in the above studies, including in regrad to clinical efficacy, bacteriological analysis, or safety. Based on the above results, we concluded that the optimal clinical dose for PZFX mesilate is 600 mg or 1, 000mg twice a day for the indication of bacterial pneumonia.